Is mitotic rate still useful in the management of patients with thin melanoma?. (22nd August 2017) - Tejera‐Vaquerizo, A.; Pérez‐Cabello, G.; Marínez‐Leborans, L.; Gallego, E.; Oliver‐Martínez, V.; Martín‐Cuevas, P.; Arias‐Santiago, S.; Aneiros‐Fernández, J.; Herrera‐Acosta, E.; Traves, V.; Herrera‐Ceballos, E.; Nagore, E.
Abstract: Background: T1 melanoma substaging was recently modified by the American Joint Committee on Cancer (AJCC). Although sentinel lymph node (SLN) positivity is the most important prognostic factor in melanoma, there is a lack of consensus on whether SLN biopsy should be performed in patients with thin melanoma (≤1 mm). Objective: The main aim of this study was to investigate predictors of SLN positivity in patients with thin melanoma, with a special emphasis on mitotic rate. A secondary aim was to evaluate survival in this group of patients. Materials and Methods: Retrospective multicenter observational study with analysis of age, sex, tumour location, thickness, mitotic rate, regression and microscopic satellites. Predictive factors were identified using a classification and regression tree (CART) approach. Melanoma‐specific survival according to SLN status was estimated using Kaplan–Meier curves. Results: We analysed 203 patients with a melanoma ≤1 mm. Using the new AJCC staging criteria, the CART algorithm identified a 7.5% likelihood of SLN positivity in T1a patients. In the case of T1b melanoma, there was a 14.3% likelihood of SLN positivity in patients with a mitotic rate >1 mitosis/mm 2 and a 3.2% likelihood in those with ≤1 mitoses/mm 2 . None of the patients with T1b disease who had ≤1 mitoses/mm 2 and regression had SLN positivity. In T1b patients, 5‐year melanoma‐specific survival was 98.7% in the SLN‐negative group and 75% in the SLN‐positive group ( P = 0.05). When stratified by mitotic rate, survival was 100% for patients with a mitotic rate of ≤1 mitoses/mm 2 and 91.4% for those with >1 mitosis/mm 2 ( P = 0.022). There were no deaths in the T1a subgroup. Conclusions: Sentinel lymph node metastasis was less common in patients with T1b melanoma who had a mitotic rate of ≤1 mitoses/mm 2 . Performance of SLN biopsy should be carefully considered in this subgroup of patients, particularly considering the good prognosis.